Preparation method of honeycomb-shaped N-CNTs composite wave-absorbing material

Through the preparation of honeycomb N-CNTs composite absorbing materials, nitrogen-doped carbon nanotubes and carbon fiber mesh structures are used to entangle each other, solving the problem of poor absorption performance of existing one-dimensional materials, significantly improving the absorption effect of electromagnetic waves and Impedance matching enables more effective electromagnetic wave shielding.

CN119212355APending Publication Date: 2024-12-27SHENZHEN SUNWAY COMM
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411064367.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing one-dimensional materials exhibit poor absorption performance in absorbing electromagnetic waves, especially due to the problem of high carrier mobility and impedance matching.

Method used

Using the preparation method of honeycomb N-CNTs composite absorbing material, nitrogen-doped carbon nanotubes are obtained through primary calcination, which increases their conductivity and charge transfer capabilities, and forms a carbon fiber mesh structure and N-CNTs mesh through secondary calcination. The structures are entangled with each other to form a dense carbon fiber N-CNTs complex, enhancing the absorption effect.

Benefits of technology

It significantly improves the shielding effect and absorption performance of electromagnetic waves. By increasing the path and opportunity of electromagnetic wave interaction with the material, the reflection and penetration of electromagnetic waves are reduced, and the electromagnetic impedance of composite absorbing materials is adjusted to better match the free space. impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212355A_ABST
    Figure CN119212355A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a honeycomb-shaped N-CNTs composite wave-absorbing material. N-CNTs powder is obtained through one-time calcination, the structure of the carbon nano tube can be improved through the nitrogen-doped carbon nano tube, the polarization phenomenon in the carbon nano tube is increased, the conductivity and the charge transmission capacity of the carbon nano tube are improved, and reflection and penetration of electromagnetic waves are reduced. And through secondary calcination, the calcined carbon fibers and the N-CNTs are intertwined to form a compact net-shaped structure. As the whole composite wave-absorbing material is in a honeycomb shape, a plurality of cavities and interfaces exist in the honeycomb structure, and the carbon fibers and the N-CNTs can be uniformly distributed on the inner walls and the outer surfaces of the cavities of the honeycomb structure, so that incident electromagnetic waves are reflected and scattered for multiple times in the structures; and the path and opportunity of interaction between electromagnetic waves and the material are increased, so that the absorption effect is improved. The honeycomb structure can also adjust the electromagnetic impedance of the composite wave-absorbing material, so that the composite wave-absorbing material can be better matched with the impedance of a free space, and the reflection of electromagnetic waves is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of absorbing materials, and in particular to a method for preparing a honeycomb N-CNTs composite absorbing material. Background Art

[0002] With the rapid development of electronic information technology, electronic equipment is widely used in military, commercial, civil communications and other fields, and the electromagnetic pollution caused by it is becoming increasingly serious. The development of lightweight and efficient anti-electromagnetic interference materials is crucial to reduce electromagnetic wave pollution.

[0003] One-dimensional materials such as carbon nanotubes (CNTs) and silver nanowires (AgNWs) have good conductivity and high aspect ratio, and their nanoscale size and high specific surface area can provide a large number of interfaces, enhance interface polarization and scattering effects, and are conducive to constructing multiple loss paths for electromagnetic waves, and enhance the absorption and attenuation of electromagnetic waves. However, the above-mentioned one-dimensional materials themselves have high carrier mobility, poor impedance matching, and poor absorption of electromagnetic waves. Summary of the invention

[0004] The embodiment of the present application provides a method for preparing a honeycomb N-CNTs composite absorbing material, aiming to improve the problem of poor absorbing performance of the absorbing material.

[0005] In the first aspect, the embodiment of the present application provides a method for preparing a honeycomb N-CNTs composite absorbing material, comprising mixing carbon nanotube powder and melamine powder, grinding and calcining once to obtain a first composite. Para-aramid fiber, dimethyl sulfoxide and sodium hydroxide are mixed to obtain an aramid fiber dispersion. The first composite is added to a first solvent and mixed evenly to obtain a first composite dispersion, the first composite dispersion is mixed with the aramid fiber dispersion, and the first composite dispersion is filtered after cooling to obtain a first gel. The first gel is filled in a regular hexagonal hollow mold, and then pre-oxidized, and the first gel after pre-oxidation is calcined twice to obtain the honeycomb N-CNTs composite absorbing material.

[0006] In some embodiments, the mixing of the carbon nanotube powder and the melamine powder and then grinding and calcining once comprises mixing the carbon nanotube powder and the melamine powder and then grinding, placing the mixture in an inert gas environment, and calcining it in a tube furnace at a temperature of 300° C. to 500° C. for 2 to 3 hours, wherein the heating rate of the tube furnace is 5° C. / min to 10° C. / min. The mass ratio of the carbon nanotube powder to the melamine powder is (20:1) to (10:1).

[0007] In some embodiments, the first gel after the pre-oxidation treatment is subjected to secondary calcination, including placing the first gel after the pre-oxidation treatment in an inert gas atmosphere and calcining it in a tubular furnace at a temperature of 600°C to 1000°C for 2h to 3h, and the heating rate of the tubular furnace is 2°C / min to 5°C / min.

[0008] In some embodiments, the mass ratio of the para-aramid fiber to the dimethyl sulfoxide is (1:200) to (1:150).

[0009] In some embodiments, the weight ratio of the sodium hydroxide to the para-aramid fiber is (1:2) to (1:1). The concentration of the sodium hydroxide is 0.5 g / ml.

[0010] In some embodiments, the volume ratio of the aramid fiber dispersion to the first composite dispersion is (30:1) to (20:1).

[0011] In some embodiments, the length of the para-aramid fiber is 3 cm to 5 cm.

[0012] In some embodiments, the concentration of the first composite dispersion is 5 mg / ml to 10 mg / ml.

[0013] In some embodiments, the first gel is filled into a regular hexagonal hollow mold and then pre-oxidized, including filling the first gel into a regular hexagonal hollow mold, drying it at a temperature of 60°C to 100°C for 2h to 3h, and then pre-oxidizing the dried first gel in an oven at a temperature of 200°C to 250°C for 2h to 3h.

[0014] In some embodiments, the inert gas includes nitrogen and / or argon.

[0015] Different from the situation of the related art, the embodiment of the present application provides a method for preparing a honeycomb N-CNTs composite absorbing material. Nitrogen-doped carbon nanotube (N-CNTs) powder is obtained by calcining once. Nitrogen-doped carbon nanotubes can improve the structure of carbon nanotubes, increase their electrical conductivity and charge transfer capacity, effectively conduct and dissipate electromagnetic energy, reduce the reflection and penetration of electromagnetic waves, thereby enhancing the shielding effect of electromagnetic waves. And the introduction of nitrogen atoms will lead to an increase in the polarization phenomenon inside the carbon nanotubes, generate more heat dissipation at different interfaces, and help to convert the incident electromagnetic wave energy into other forms such as heat, thereby reducing the propagation of electromagnetic waves. Through secondary calcination, the para-aramid fiber forms a carbon fiber mesh structure after secondary calcination, and is entangled with the N-CNTs mesh structure to form a dense carbon fiber N-CNTs complex. The para-aramid fiber itself has a high carbon content and is composed of an alternating linear chain of amide bonds and benzene rings. The carbon fiber formed after calcination is combined with N-CNTs to form a mesh structure with high strength and stable structure. Since the honeycomb N-CNTs composite absorbing material in the present application is honeycomb-shaped as a whole, there will be many chambers and interfaces inside the honeycomb structure, and the carbon fiber mesh structure and the N-CNTs mesh structure can be relatively evenly distributed on the inner wall and outer surface of the chamber of the honeycomb structure. The honeycomb structure combined with the mesh structure formed by carbon fiber and N-CNTs allows the incident electromagnetic waves to experience multiple reflections and scattering in these structures, increasing the path and opportunity for the electromagnetic waves to interact with the material, thereby improving the absorption effect. The honeycomb structure combined with the mesh structure can also adjust the electromagnetic impedance of the composite absorbing material to better match the impedance of the free space, reduce the reflection of electromagnetic waves, and promote more energy to enter the composite absorbing material and be absorbed. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] One or more embodiments are exemplarily described by corresponding drawings, which do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and the figures in the drawings do not constitute proportional limitations unless otherwise stated.

[0017] Figure 1 It is a flow chart of a method for preparing some honeycomb N-CNTs composite absorbing materials provided in the embodiments of the present application;

[0018] Figure 2 It is a schematic diagram of the structure of some honeycomb N-CNTs composite absorbing materials provided in the embodiments of the present application;

[0019] Figure 3 This is an embodiment of the present application Figure 2 A magnified schematic diagram of center A. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "several" and "multiple" is more than two, unless otherwise clearly and specifically defined.

[0022] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0023] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. In addition, the technical features involved in the different embodiments of the present application described below may be combined with each other as long as they do not conflict with each other.

[0024] In the first aspect, the present application embodiment provides a method for preparing a honeycomb N-CNTs composite absorbing material, please refer to Figure 1 , Figure 1 Flow chart of some preparation methods of honeycomb N-CNTs composite absorbing materials provided in the embodiments of the present application. The preparation method comprises the following steps:

[0025] Step S1: mixing carbon nanotube powder and melamine powder, grinding and calcining them once to obtain a first composite.

[0026] Carbon nanotubes (CNTs) powder is made of a large number of carbon nanotubes. Carbon nanotubes are a one-dimensional quantum material with a special structure. Its radial size is nanometers and its axial size is micrometers. Both ends of the carbon nanotubes are basically sealed. Carbon nanotubes are mainly composed of coaxial cylinders with several to dozens of layers of carbon atoms arranged in hexagons. Carbon nanotubes have excellent mechanical, electrical and chemical properties, such as high strength, high conductivity, good thermal stability, etc. They are widely used in composite materials, electronics, and energy fields.

[0027] Melamine powder is a triazine-type nitrogen-containing heterocyclic organic compound, usually a white odorless powder. Melamine contains three single atoms, of which the nitrogen content reaches 66.7%. It is commonly used in the plastics industry, flame retardants and other industries.

[0028] The first composite material is obtained by mixing carbon nanotube powder and melamine powder and then calcining them once. The first composite material is nitrogen-doped carbon nanotube (N-CNTs) powder. Nitrogen-doped carbon nanotubes can improve the structure of carbon nanotubes, increase their electrical conductivity and charge transfer capacity, effectively conduct and dissipate electromagnetic energy, and reduce the reflection and penetration of electromagnetic waves by enhancing the electrical conductivity of carbon nanotubes, thereby enhancing the shielding effect of electromagnetic waves. The introduction of nitrogen atoms will increase the polarization phenomenon inside the carbon nanotubes, and generate more heat dissipation at different interfaces, which will help convert the incident electromagnetic wave energy into other forms such as heat, thereby reducing the propagation of electromagnetic waves. In addition, nitrogen atoms can change the microstructure and morphology of carbon nanotubes, forming a more complex network or stacking structure, thereby increasing the reflection path and absorption path of electromagnetic waves and enhancing the loss of electromagnetic waves.

[0029] In some embodiments, the mixing of carbon nanotube powder and melamine powder and grinding for a calcination includes mixing carbon nanotube powder and melamine powder and grinding, placing in an inert gas environment, and calcining in a tube furnace at a temperature of 300° C. to 500° C. for 2 hours to 3 hours, and the heating rate of the tube furnace is 5° C. / min to 10° C. / min. The mass ratio of carbon nanotube powder to melamine powder is (20:1) to (10:1). The inert gas includes nitrogen and / or argon.

[0030] Step S2: mixing para-aramid fiber, dimethyl sulfoxide and sodium hydroxide to obtain an aramid fiber dispersion.

[0031] Para-aramid fiber, full name poly(p-phenylene terephthalamide) fiber, is a high-performance synthetic fiber with high strength, high modulus, light weight, high temperature resistance, chemical corrosion resistance and other properties.

[0032] Dimethyl sulfoxide promotes the dispersion of para-aramid fibers by weakening the hydrogen bonds and other intermolecular forces between the para-aramid fibers, making them evenly distributed in the system.

[0033] Sodium hydroxide can promote the modification of the surface of para-aramid fiber and improve the compatibility and dispersibility of para-aramid fiber in the system.

[0034] In some embodiments, the mass ratio of the para-aramid fiber to dimethyl sulfoxide is (1:200) to (1:150).

[0035] In some embodiments, the weight ratio of sodium hydroxide to para-aramid fiber is (1:2) to (1:1), and the concentration of sodium oxide is 0.5 g / ml.

[0036] In some embodiments, the para-aramid fibers are 3 cm to 5 cm in length.

[0037] By mixing para-aramid fiber, dimethyl sulfoxide and sodium hydroxide, well-dispersed aramid fiber dispersion (ANFs) can be obtained for subsequent use.

[0038] Step S3: adding the first composite into the first solvent and mixing them evenly to obtain a first composite dispersion, mixing the first composite dispersion with the aramid fiber dispersion, cooling and filtering, and obtaining a first gel.

[0039] Among them, the first gel is ANFs / N-CNTs hydrogel.

[0040] The first composite is added to a first solvent for dispersion, and the first solvent may be one or more of sodium hydroxide solution, potassium hydroxide solution, dimethyl sulfoxide, ethanol, acetone, acetaldehyde, etc. Before the first composite dispersion is mixed and dispersed with the aramid fiber dispersion, the concentration of the first composite dispersion is adjusted to 5 mg / ml to 10 mg / ml so that the first composite dispersion and the aramid fiber dispersion can be fully mixed.

[0041] In some embodiments, the volume ratio of the aramid fiber dispersion to the first composite dispersion is (30:1) to (20:1).

[0042] Step S4: Fill the first gel into a regular hexagonal hollow mold, perform a pre-oxidation treatment, and perform a secondary calcination on the pre-oxidation treated first gel to obtain a honeycomb N-CNTs composite absorbing material.

[0043] The first gel has a certain fluidity and can be filled in a regular hexagonal hollow mold. For example, the regular hexagonal hollow mold can be a regular hexagonal nylon column. The first gel fixed in the mold is subjected to secondary calcination to form a composite absorbing material with an appearance similar to a honeycomb. In order to maintain the stability of the first gel structure, the first gel can be filled in the regular hexagonal hollow mold and pre-oxidized. After the pre-oxidation, the fixed first gel is taken out and then calcined again.

[0044] In some embodiments, the first gel is filled into a regular hexagonal hollow mold and then pre-oxidized, including filling the first gel into a regular hexagonal hollow mold, drying it at a temperature of 60°C to 100°C for 2h to 3h, and then pre-oxidizing the dried first gel in an oven at a temperature of 200°C to 250°C for 2h to 3h.

[0045] Pre-oxidation treatment is a process for pre-treating materials under specific conditions, aiming to improve the performance of the material or prepare for subsequent treatment. In the embodiment of the present application, pre-oxidation treatment of the first gel can introduce some stable chemical bonds or functional groups into the molecular structure of the first gel, thereby improving its stability in a high temperature environment, reducing thermal decomposition and thermal deformation, and preparing for subsequent calcination. In addition, the first gel contains more carbon raw materials. Through pre-oxidation treatment, the structure of the carbon fibers in the prepared composite absorbing material is more uniform and dense, and the overall mechanical strength and hardness are higher.

[0046] In some embodiments, the first gel after pre-oxidation is subjected to secondary calcination, comprising: placing the first gel after pre-oxidation in an atmosphere of inert gas, calcining in a tubular furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, and the heating rate of the tubular furnace is 2° C. / min to 5° C. / min. The inert gas includes nitrogen and / or argon.

[0047] It should be noted that the above-mentioned primary calcination refers to the first calcination process, and the secondary calcination refers to the second calcination process. The above-mentioned primary and secondary refer to the operation steps, not the number of operations.

[0048] Please refer to Figure 2 and Figure 3 , the para-aramid fiber in the first gel provides part of the carbon source to compound with N-CNTs during the secondary calcination process, and the para-aramid fiber forms a carbon fiber mesh structure 11 after the secondary calcination, and is entangled with the N-CNTs mesh structure 12 to form a dense carbon fiber N-CNTs complex. In particular, the para-aramid fiber itself has a high carbon content and is composed of an alternating linear chain of amide bonds and benzene rings. The carbon fiber formed after calcination is combined with the N-CNTs to form a mesh structure with high strength and stable structure. Since the honeycomb N-CNTs composite absorbing material 10 in the present application is honeycomb-shaped as a whole, there will be many chambers and interfaces inside the honeycomb structure. The carbon fiber mesh structure 11 and the N-CNTs mesh structure 12 can be more evenly distributed on the inner wall and outer surface of the chamber of the honeycomb structure. The honeycomb structure is combined with the mesh structure formed by carbon fibers and N-CNTs so that the incident electromagnetic waves experience multiple reflections and scatterings in these structures, which increases the path and opportunity for the electromagnetic waves to interact with the material, thereby improving the absorption effect. The honeycomb structure combined with the mesh structure can also adjust the electromagnetic impedance of the composite absorbing material to make it better match the impedance of free space, reduce the reflection of electromagnetic waves, and promote more energy to enter the composite absorbing material and be absorbed.

[0049] In addition, the carbon fibers and honeycomb structure formed by the para-aramid fibers make the honeycomb N-CNTs composite absorbing material prepared in the embodiment of the present application lightweight. While providing good absorbing performance, it can meet some scenarios with strict requirements on weight, such as aerospace, railway transportation and other fields.

[0050] The embodiment of the present application provides a honeycomb N-CNTs composite absorbing material, and a first composite is obtained by a single calcination, and the first composite is a nitrogen-doped carbon nanotube (N-CNTs) powder. The nitrogen-doped carbon nanotube can improve the structure of the carbon nanotube, increase its conductivity and charge transfer capacity, effectively conduct and dissipate electromagnetic energy, reduce the reflection and penetration of electromagnetic waves, and thus enhance the shielding effect of electromagnetic waves. And the introduction of nitrogen atoms will lead to an increase in the polarization phenomenon inside the carbon nanotube, generate more heat dissipation at different interfaces, and help to convert the incident electromagnetic wave energy into other forms such as heat, thereby reducing the propagation of electromagnetic waves. Through secondary calcination, the para-aramid fiber is calcined to form a carbon fiber mesh structure 11, which is intertwined with the N-CNTs mesh structure 12 to form a dense carbon fiber N-CNTs composite. In particular, the para-aramid fiber itself has a high carbon content and is composed of an alternating linear chain of amide bonds and benzene rings. The carbon fiber formed after calcination is combined with the N-CNTs to form a mesh structure with high strength and stable structure. Since the honeycomb N-CNTs composite absorbing material 10 in the present application is honeycomb-shaped as a whole, there are many chambers and interfaces inside the honeycomb structure, and the carbon fiber mesh structure 11 and the N-CNTs mesh structure 12 can be relatively evenly distributed on the inner wall and outer surface of the chamber of the honeycomb structure. The honeycomb structure combined with the mesh structure formed by carbon fiber and N-CNTs allows the incident electromagnetic waves to experience multiple reflections and scatterings in these structures, increasing the paths and opportunities for electromagnetic waves to interact with the material, thereby improving the absorption effect. The honeycomb structure combined with the mesh structure can also adjust the electromagnetic impedance of the composite absorbing material to better match the impedance of free space, reduce the reflection of electromagnetic waves, and promote more energy to enter the composite absorbing material and be absorbed.

[0051] In a second aspect, an embodiment of the present application further provides an electronic device, which includes a honeycomb N-CNTs composite absorbing material prepared by the preparation method of the first aspect. The honeycomb N-CNTs composite absorbing material can be used for the housing of an electronic device, or a specific surface of an electronic device, to effectively block interference from external electromagnetic waves, while preventing electromagnetic waves generated inside the device from radiating outward, thereby ensuring the normal operation of the device and reducing electromagnetic pollution.

[0052] The preparation method of the honeycomb N-CNTs composite absorbing material is described below in conjunction with a specific embodiment:

[0053] Example 1

[0054] (1) 3 cm of para-aramid fiber, dimethyl sulfoxide and sodium hydroxide were uniformly mixed to obtain an aramid fiber dispersion, wherein the mass ratio of the para-aramid fiber to the dimethyl sulfoxide was 1:200, the concentration of the sodium hydroxide solution was 0.5 g / mL, and the addition ratio of the sodium hydroxide solution to the para-aramid fiber was 1 mL:1 g.

[0055] (2) After 1 g of carbon nanotube powder and 0.05 g of melamine powder were fully ground, the mixture was placed at 400 °C and N 2 The first composite was obtained by calcining in a tubular furnace for 2 h, wherein the heating rate in the tubular furnace was 5° C. / min.

[0056] (3) The first composite is prepared into a first composite dispersion with a concentration of 5 mg / mL, and then 450 ml of the aramid fiber dispersion is fully mixed with 20 ml of the first composite dispersion. After cooling to room temperature, vacuum filtration is performed to obtain a first gel.

[0057] (4) The hexagonal nylon columns were uniformly inserted into the first gel, and dried at 80°C for 2 h. The dried first gel was then placed in an oven at 230°C for pre-oxidation for 2 h. The pre-oxidized first gel was placed at 800°C and N 2 The carbonization was carried out in a tubular furnace for 2 h, wherein the heating rate of the tubular furnace was 2°C / min, and a honeycomb N-CNTs composite absorbing material was obtained after natural cooling.

[0058] Example 2

[0059] (1) 5 cm of para-aramid fiber, dimethyl sulfoxide and sodium hydroxide were uniformly mixed to obtain an aramid fiber dispersion, wherein the mass ratio of the para-aramid fiber to the dimethyl sulfoxide was 1:150, the concentration of the sodium hydroxide solution was 0.5 g / mL, and the addition ratio of the sodium hydroxide solution to the para-aramid fiber was 0.5 mL:1 g.

[0060] (2) After 1 g of carbon nanotube powder and 0.1 g of melamine powder were fully ground, the mixture was placed at 450 °C and N 2 The first composite was obtained by calcining in a tubular furnace for 2 h, wherein the heating rate in the tubular furnace was 5° C. / min.

[0061] (3) The first composite is prepared into a first composite dispersion with a concentration of 10 mg / mL, and then 400 ml of the aramid fiber dispersion is fully mixed with 15 ml of the first composite dispersion. After cooling to room temperature, vacuum filtration is performed to obtain a first gel.

[0062] (4) The hexagonal nylon columns were uniformly inserted into the first gel, and dried at 80°C for 2 h. The dried first gel was then placed in an oven at 200°C for pre-oxidation for 2 h. The pre-oxidized first gel was placed at 900°C and N 2 The carbonization was carried out in a tubular furnace for 2 h, wherein the heating rate of the tubular furnace was 2°C / min, and a honeycomb N-CNTs composite absorbing material was obtained after natural cooling.

[0063] Comparative Example 1

[0064] (1) 3 cm of para-aramid fiber, dimethyl sulfoxide and sodium hydroxide were uniformly mixed to obtain an aramid fiber dispersion, wherein the mass ratio of the para-aramid fiber to the dimethyl sulfoxide was 1:200, the concentration of the sodium hydroxide solution was 0.5 g / mL, and the addition ratio of the sodium hydroxide solution to the para-aramid fiber was 1 mL:1 g.

[0065] (2) After 1 g of carbon nanotube powder and 0.05 g of melamine powder were fully ground, the mixture was placed at 400 °C and N 2 The first composite was obtained by calcining in a tubular furnace for 2 h, wherein the heating rate in the tubular furnace was 5° C. / min.

[0066] (3) The first composite is prepared into a first composite dispersion with a concentration of 5 mg / mL, and then 450 ml of the aramid fiber dispersion is fully mixed with 20 ml of the first composite dispersion. After cooling to room temperature, vacuum filtration is performed to obtain a first gel.

[0067] (4) The first gel was dried at 80°C for 2 h, and then the dried first gel was pre-oxidized in an oven at 230°C for 2 h. The pre-oxidized first gel was placed at 800°C and N 2 The carbonized samples were carbonized in a tubular furnace for 2 h, wherein the heating rate of the tubular furnace was 2°C / min, and the N-CNTs composite absorbing material was obtained after natural cooling.

[0068] Comparative Example 2

[0069] (1) After 1 g of carbon nanotube powder and 0.05 g of melamine powder were fully ground, the mixture was placed at 400 °C and N 2 The first composite was obtained by calcining in a tubular furnace for 2 h, wherein the heating rate in the tubular furnace was 5° C. / min.

[0070] (2) The first complex is prepared into a first complex dispersion with a concentration of 5 mg / mL, cooled to room temperature, and then vacuum filtered to obtain a second complex.

[0071] (3) The hexagonal nylon columns were uniformly inserted into the second composite, dried at 80°C for 2 h, and then the dried second composite was placed in an oven at 230°C for pre-oxidation for 2 h. The pre-oxidized second composite was placed at 800°C and N 2 The carbonization was carried out in a tubular furnace for 2 h, wherein the heating rate of the tubular furnace was 2°C / min, and a honeycomb N-CNTs composite absorbing material was obtained after natural cooling.

[0072] The wave absorbing performance of the composite wave absorbing materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 was tested respectively.

[0073] The minimum reflection loss value RL when the thickness of the composite absorbing material in Example 1 is 1.92 mm min It is -38.4dB, and the effective absorption band is 4.50GHz.

[0074] The minimum reflection loss value RL when the thickness of the composite absorbing material in Example 2 is 2.35 mm min It is -42.8dB, and the effective absorption band is 4.26GHz.

[0075] The minimum reflection loss value RL when the thickness of the composite absorbing material in Comparative Example 1 is 3.05 mm min It is -25.7dB, and the effective absorption band is 2.9GHz.

[0076] The minimum reflection loss value RL when the thickness of the composite absorbing material in Comparative Example 2 is 2.9 mm min It is -29.8dB, and the effective absorption band is 3.5GHz.

[0077] According to the test results of the absorbing performance, by comparing the above embodiments and the comparative example, it can be seen that the composite absorbing materials in Embodiment 1 and Embodiment 2 have a stronger absorption capacity for electromagnetic waves, and the composite absorbing materials in Embodiment 1 and Embodiment 2 can absorb a wider range of electromagnetic frequencies, effectively reducing the radiation effect of electromagnetic waves.

[0078] By comparing Example 1 and Comparative Example 1, the composite absorbing material in Comparative Example 1 is a non-cellular structure, and the non-cellular composite absorbing material has relatively fewer cavities and interfaces. It is difficult for electromagnetic waves to be reflected and scattered more in the non-cellular composite absorbing material, and the paths and opportunities for electromagnetic waves to interact with the composite absorbing material are reduced, so that the absorbing performance of the composite absorbing material in Comparative Example 1 is weaker than that of the composite absorbing material in Example 1, and the absorption effect is not good.

[0079] By comparing Example 1 and Comparative Example 2, no para-aramid fiber is added in the process of preparing the composite absorbing material in Comparative Example 2, and there is no carbon fiber with a mesh structure on the surface of N-CNTs in the composite absorbing material structure. Since the carbon fiber with a microstructure can increase the reflection and scattering path of electromagnetic waves, and can also adjust the electromagnetic impedance of the composite absorbing material, reduce the impedance mismatch, and reduce the reflection of electromagnetic waves. Therefore, compared with Example 1, the composite absorbing material in Comparative Example 2 has poor absorption of electromagnetic waves.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a honeycomb N-CNTs composite absorbing material, characterized in that: include: The carbon nanotube powder and the melamine powder are mixed, ground and calcined once to obtain a first composite; The para-aramid fiber, dimethyl sulfoxide and sodium hydroxide are mixed to obtain an aramid fiber dispersion; adding the first complex to a first solvent and mixing evenly to obtain a first complex dispersion, mixing the first complex dispersion with the aramid fiber dispersion, cooling and filtering to obtain a first gel; The first gel is filled into a regular hexagonal hollow mold, and then pre-oxidation treatment is performed, and the first gel after the pre-oxidation treatment is secondary calcined to obtain the honeycomb N-CNTs composite absorbing material.

2. The preparation method according to claim 1, characterized in that: The method of mixing the carbon nanotube powder and the melamine powder, grinding them and then calcining them once comprises: The carbon nanotube powder and melamine powder are mixed and ground, and then placed in an inert gas environment and calcined in a tube furnace at a temperature of 300° C. to 500° C. for 2 h to 3 h, and the heating rate of the tube furnace is 5° C. / min to 10° C. / min; The mass ratio of the carbon nanotube powder to the melamine powder is (20:1) to (10:1).

3. The preparation method according to claim 1, characterized in that: The first gel after the pre-oxidation treatment is subjected to secondary calcination, comprising: The first gel after the pre-oxidation treatment is placed in an inert gas atmosphere and calcined in a tubular furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, and the heating rate of the tubular furnace is 2° C. / min to 5° C. / min.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the para-aramid fiber to the dimethyl sulfoxide is (1:200) to (1:150).

5. The preparation method according to claim 1, characterized in that: The weight ratio of the sodium hydroxide to the para-aramid fiber is (1:2) to (1:1); The concentration of the sodium hydroxide is 0.5 g / ml.

6. The preparation method according to claim 1, characterized in that: The volume ratio of the aramid fiber dispersion to the first composite dispersion is (30:1) to (20:1).

7. The preparation method according to claim 1, characterized in that: The length of the para-aramid fiber is 3 cm to 5 cm.

8. The preparation method according to claim 1, characterized in that: The concentration of the first composite dispersion is 5 mg / ml to 10 mg / ml.

9. The preparation method according to claim 1, characterized in that: The step of filling the first gel into a regular hexagonal hollow mold and then performing a pre-oxidation treatment comprises: The first gel is filled into a regular hexagonal hollow mold, and dried at a temperature of 60° C. to 100° C. for 2 h to 3 h. The dried first gel is then placed in an oven at a temperature of 200° C. to 250° C. for pre-oxidation for 2 h to 3 h.

10. The preparation method according to claim 2, characterized in that: The inert gas includes nitrogen and / or argon.

Citation Information

Cited By

  • Controller circuit board for street lamp based on nano heat dissipation material and preparation method of controller circuit board

    CN122534749A

  • A controller circuit board for a street lamp based on a nano heat dissipation material and a preparation method thereof

    CN122534749B